Two stars for comfort - Mortimer, John; Howard, Trevor, 1916-1988.; Elliott, Michael, 1931-; Pride, Malcolm; Pilbrow, Richard; Mortimer, John, 1923-2009.; Garrick Theatre (London, England); Richard L. Coe Theater Programs Collection (Library of Congress) (Lopndon : Mathuen and ltd., 1962)
Garrick Theatre, Michael Codron and David Hall present Trevor Howard in "Two Stars For Comfort," a new play by John Mortimer, the play directed by Michael Elliott, setting by Malcolm Pride, lighting by Richard Pilbrow.
Garrick Theatre, Charing Cross Road, W.C. 2, the first performance at this theatre, Wednesday, 4th April, 1962.
Title devised by Library staff.
Cast: Esmond Knight, Gabriella Licudi, Diane Clare, Anthony Valentine, David Walsh, Trevor Howard, Patricia Healey, Isabel Dean, Hazel Hughes, Peter Sallis, Dudley Jones, Noel Howlett, William Fox.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Drama; Theater programs -- England -- London; Theater programs